Does green finance affect renewable energy development in Singapore? - Yogeeswari Subramaniam; Nanthakumar Loganathan (Journal of Asian Business and Economic Studies)
Purpose – Given the importance of green finance in a discussion of energy efficiency and clean energy, it is critical to evaluate its implications for the growth of renewable energy. This study examines the impact of green finance on renewable energy development in Singapore. Design/methodology/approach – The dynamic ordinary least squares (DOLS) regression was used in this work to test such a connection. Findings – Using the DOLS for the period 2000–2020, it was discovered that green finance aids renewable energy development in Singapore. Additionally, the findings revealed that economic growth, oil prices, energy consumption, carbon dioxide emissions and institutional factors are all positively associated with renewable energy growth, resulting in a boost in renewable energy development. Research limitations/implications – Hence, as a result, the monetary authorities of Singapore, such as financial institutions, non-governmental organisations and corporations, should prioritise renewable energy projects under green finance initiatives to boost renewable energy growth. This may assist in raising investment flows to green projects; hence, accelerating the adoption of renewable energy. Originality/value – Increased Singapore's initiatives to accelerate green finance have prompted this study to examine the research question of whether green finance has a significant impact on renewable energy growth. Thus, to the best of the authors’ knowledge, this will be the first empirical study to explore the impact of green finance on renewable energy growth in the case of Singapore.